Case Report: Autoimmune Pemphigus Vulgaris in a Patient Treated With Cemiplimab for Multiple Locally Advanced Cutaneous Squamous Cell Carcinoma - Buquicchio, Rosalba; Mastrandrea, Valentina; Strippoli, Sabino; Quaresmini, Davide; Guida, Michele; Filotico, Raffaele (Frontiers in Oncology, 2021)
Background: Pemphigus vulgaris (PV) is a rare and severe autoimmune blistering disorder affecting the skin and mucous membranes, characterized by the production of autoantibodies against two desmosomal adhesion proteins, desmoglein 1 and 3. In patients with advanced squamous cell carcinoma of the skin unfit for surgery and radiotherapy, immune check-point inhibitors including the anti-Programmed Death-1 (PD-1) agent cemiplimab have been successfully employed proving relevant clinical outcomes. Cemiplimab is a monoclonal antibody capable of inhibiting PD-1 signaling that has recently been approved for the treatment of patients with metastatic or locally advanced cutaneous squamous cell carcinoma. Although the peculiar setting of advanced CSCC involving elderly patients, rare and unusual skin immune-related adverse events such as PV could be observed in cemiplimab treated patients. Case report: A 95-year-old man without a history of autoimmune disease was treated with cemiplimab for multiple and advanced squamous cell carcinomas of the head obtaining a complete response to therapy. After seven cycles of cemiplimab administered every 21 days the patient developed a mucocutaneous blistering eruption. Clinical diagnosis of PV was suspected on the basis of the diffuse involvement of trunk and extremities with large blisters, and necrotic eschar. It was carried out an ELISA test, that showed high level of circulating antibodies against desmoglein 1, thus confirming the diagnosis of PV. For this reason, cemiplimab infusion was discontinued and complete resolution of skin lesions was obtained using oral prednisone 0,8 mg/kg/daily for four weeks. Once remission was achieved, a maintenance dose of 10 mg/day was administered, observing a good control of bullous disease and low value of desmoglein 1. Response to CSCC persisted also during cemiplimab discontinuation, until obtaining a complete remission still persisting at 9 months after the last cycle of therapy. Conclusion: The case we observed is the first description of PV revealed from cemiplimab therapy, thus suggesting that cemiplimab could allow the arise of underlying autoimmune PV, through a mechanism both T and B-cell-mediated.